FORMULASI TABLET KUYAH DARI MINYAK ATSIRI JERUK KALAMANSI (Citrofortunella microcarpa) DENGAN VARIASI PEMANIS SORBITOL - Aina Fatkhil Haque; Elly Mulyani; Dewi Winni Fauziah; Joeis Joeis (SINTA Journal (Science, Technology, and Agricultural), 2023)
In the essential oil of calamansi orange peel, the main component is limonene, which is known to have antimicrobial and antiseptic activity. The chewable tablet dosage form is considered suitable to be combined with calamansi orange essential oil which has been proven to have antibacterial properties, so it is necessary to add variations of sorbitol sweetener. The general objective of this research is to obtain chewable tablets that have good physical properties and taste that are accepted by the market. This study examined (1) the physical evaluation test of all chewable tablet formulations meeting the physical evaluation requirements (weight uniformity test, size uniformity test, and taste response test) (2) taste response test was carried out on variations in the use of sorbitol. The chewable tablets were formulated in 3 groups, FI (Sorbitol 50%), FII (sorbitol : 60%) and FIII (Sorbitol : 70%), and the formulation of the chewable tablets used the direct compression method. The test results for the physical properties of the tablets showed that all tablets met the requirements. The effect on the use of sorbitol in the formulation increased the hardness, friability, and sweetness of the tablets, but had no effect on the uniformity of the weight and uniformity of the size of the tablets. The formulation of the chewable tablet which was very good was seen from the results of the physical properties test and the taste response of the tablet and the best formulation was Formula III